Biomass-derived activated carbon material from native European deciduous trees as an inexpensive and sustainable energy material for supercapacitor application - Jain, Amrita; Ghosh, Meena; Krajewski, Marcin; Kurungot, Sreekumar; Michalska, Monika (Journal of Energy Storage, 2021)
Activated carbons are one of the possible electrode materials for supercapacitors (SCs), which are widely used in commercial applications. Herein, we reported the synthesis of a novel activated carbon derived through a cavitation process from the mixture of native European deciduous trees, Birch, Fagaceae, and Carpinus betulus (commonly known as European hornbeam), which was employed as the electrode material in SC. From the morphological and structural characterization, we observed that the prepared sample is a desirable carbon with good porosity and high specific surface area of about 614 m(2) g(-1). The electrochemical properties of the synthesized material were evaluated with a three-electrode configuration in 1.0 M H2SO4 electrolyte. It was found that in device mode, the carbon material delivers a specific capacitance of 24 F g(-1) at 0.25 A g(-1) with excellent cycling stability of over 10000 consecutive charge/discharge cycles. Thus, our studies demonstrate the facile synthesis of biomass-derived carbon and its application as a versatile electrode material for SC applications.
Keywords: Biomass; Carbon material; Deciduous trees; Electrode material; supercapacitor

Binder-free and flexible VOPO4/CNT film as cathode for aqueous rechargeable Zn-metal battery - Dilwale, Swati; Babu, Athira; Puthiyaveetil, Priyanka Pandinhare; Kurian, Maria; Ghosh, Meena; Kurungot, Sreekumar (Advanced Sustainable Systems, 2023)
Aqueous rechargeable Zn-metal batteries (AZMBs) are promising energy storage aids due to their inherent safety, low cost, and competent performance, with prospects in stationary and portable applications. In this regard, one of the critical requirements is developing electrodes that can adapt to mechanical deformation without compromising the charge storage performance. The current work demonstrates the development of a binder-free and mechanically flexible composite cathode film (VP/fCNT-F, where `F' stands for the film) based on VOPO4 (VP) and functionalized carbon nanotubes (fCNTs). The VP/fCNT-F film processing involves simple vacuum filtration of the composite obtained from the in-situ reaction of the fCNTs and the VP precursor in an aqueous medium. The functionalization of carbon nanotube (CNT) is important for the homogenous dispersion of VP and fCNT. The VP/fCNT-F electrode is used as a monolithic electrode in AZMB cells in combination with both liquid and quasi-solid-state gel polymer electrolytes. Besides, the utility of the VP/fCNT-F electrode in a flexible battery configuration is also demonstrated. Interestingly, in both the coin-cell and flexible configurations, the VP/fCNT-F electrode delivers a comparable discharge capacity of 90 and 78 mAh g(-1), respectively (at 0.1 A g(-1)), validating the advantage of the binder-free VP/fCNT-F electrode for AZMBs.
Keywords: binder-free cathodes; flexible batteries; layered VOPO4; polymer gel electrolytes; self-standing flexible films

Breaking the Pt electron symmetry and OH spillover towards ptir active center for performance modulation in direct ammonia fuel cell - Barik, Sidharth; Kharabe, Geeta Pandurang; Samal, Pragnya Paramita; Urkude, Rajashri R.; Kumar, Sachin; Yoyakki, Athira; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2024)
The growing interest in low-temperature direct ammonia fuel cells (DAFCs) arises from the utilization of a carbon-neutral ammonia source; however, DAFCs encounter significant electrode overpotentials due to the substantial energy barrier of the *NH2 to *NH dehydrogenation, compounded by the facile deactivation by *N on the Pt surface. In this work, a unique catalyst, Pt4Ir@AlOOH/NGr i.e., Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles controllably decorated on the pseudo-boehmite phase of AlOOH-supported nitrogen-doped reduced graphene (AlOOH/NGr) composite, synthesized via the polyol reduction method. The detailed studies on the structural and electronic properties of the catalyst by XAS and VB-XPS reveal the possible electronic modulations. The optimized Pt4Ir/ANGr composition exhibits a significantly improved onset potential and mass activity for AOR. The DFT study confirms the OHad species spillover by AlOOH and Pt4Ir (100) facilitates the conversion of the *NH2 to *NH with minimal energy barriers. Finally, testing of DAFC at the system level using a membrane electrode assembly (MEA) with Pt4Ir/ANGr as the anode catalyst, demonstrating the suitability of the catalyst for its practical applications. This study thus uncovers the potential of the Pt4Ir catalyst in synergy with ANGr, largely addressing the challenges in hydrogen transportation, storage, and safety within DAFCs. In this article, a versatile catalyst, Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles decorated on AlOOH/NGr composite. The AlOOH provides an -OH-rich surface conducive to the facile adsorption and decoration of the PtIr alloy nanoparticles and OHad species spillover from AlOOH to the Pt4Ir active center during AOR, further validating the higher experimental activity obtained in Pt4Ir/ANGr. image
Keywords: ammonia oxidation reaction (AOR); d-band center; density functional theory (DFT) study; direct ammonia fuel cells; hydroxyl spillover effect; XAS analysis

Binder-free in situ interface reconstruction of NiMoO4 nanorods over Ni(OH)2 nanosheets for efficient urea oxidation - Kumar, Yogesh; Barik, Sidharth; Kharabe, Geeta Pandurang; Torris, Arun; Singh, Mayank U.; Mohan, S.; Galave, Chaitanya; Tekawadia, Jyoti; Kanawade, Rajesh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Replacing the energy-intensive oxygen evolution reaction (OER) with the urea oxidation reaction (UOR) in electrochemical water splitting offers simultaneous green hydrogen production and urea-rich wastewater oxidation, enhancing energy efficiency and economic viability. In this study, a non-noble metal-based binder-free NiMoO4/Ni(OH)2/NF electrocatalyst is developed, featuring NiMoO4 nanorods anchored on Ni(OH)2 nanosheets. This unique morphology facilitates a highly active in situ reconstructed interface, delivering a current density of 134 mA cm-2 at 1.40 V (vs RHE) in 1 m KOH with 0.33 m urea, significantly outperforming its individual components. The catalyst demonstrates excellent stability over 50 h at 30 mA cm-2. When integrated into an anion exchange membrane urea electrolyser (13 cm2 area) with Pt@C/NF as the HER cathode, the system achieves 192 mA cm-2 at 1.60 V. The post-UOR studies confirm the presence of an amorphous NiMoO4-crystalline Ni(OH)2 interface, which plays a key role in enhancing the availability of the active sites to enhance the UOR performance. The improved electrochemical performance of the engineered catalyst can be ascribed to the in situ reconstructed amorphous-crystalline interface, optimal hydrophilicity, reduced charge transfer resistance, and the distinct morphology. This strategy offers a promising pathway for developing highly active electrocatalysts for energy conversion applications.
Keywords: AEM; electrolyser; OWS; tomography; UOR; wastewater